Efficacy of different front-of-package labeling systems in changing purchase intention and product healthfulness perception for food products in Argentina - Luciana Castronuovo; Maria Victoria Tiscornia; Leila Guarnieri; Enrique Martins; Fabio S Gomes; Lorena Allemandi (Pan American Health Organization, 2022)
Objectives. To identify the front-of-package scheme-Multiple Traffic Light (MTL), Nutri-Score (NS), and black octagon Warning System (WS)-most effective in reducing purchase intention and perceived product healthfulness of drinking yogurts, cookies and cheese spreads, and to assess the joint influence of nutrient claims on the effects. Methods. Randomized-controlled experiment. A within-subjects factorial design was used to evaluate the influence of three independent factors on perceived product healthfulness and purchase intention. A total of 704 adults in Argentina were shown three mock-up products and asked to indicate which product they would buy choosing between pairs of products from different categories and to rate product healthfulness on a 7-point Likert scale. Results. The WS was the most effective in reducing purchase intention in drinking yogurts (OR:0.16, 95%CI: 0.09;0.28), cookies (OR:0.10, 95%CI: 0.05;0.18) and cheese spreads (OR:0.10, 95%CI: 0.05;0.18), and the perception of healthfulness (WS Mean score 3,63 vs No label 4,24, p<0.001), regardless of the participants' gender, age, and level of education. NS was inefficacious in reducing product healthfulness perception, while MTL had significantly increased how healthful the product was perceived (p<0.001). Nutrient claims increased purchase intention and perception of healthfulness, thus reducing the effectiveness of front-of-package labels (p<0.001). Conclusions. In line with growing evidence, our findings support that WS perform better than NS and MTL in reducing purchase intention and healthfulness perception of products with excessive amounts of critical nutrients associated with the greatest burden of diseases. Front-of-package WS are expected to facilitate the population in Argentina to make healthier decisions.